Hydrocotyle simulans (Araliaceae), a new perennial species from south-eastern Australia - Perkins, Andrew J. (Phytotaxa, 2020)
Hydrocotyle simulans, a new perennial species from south-eastern Australia, is here described with associated illustration, photographic images and distribution map. The new species is restricted mostly to freshwater swamps in coastal areas of south-eastern South Australia, southern Victoria and to the Furneaux Group of islands, off the north-eastern coast of Tasmania. Hydrocotyle simulans resembles both H. plebeya and H. pterocarpa, in having orbicular-cordate to reniform leaves, hydathodes along leaf lamina margins and broadly ovate to orbicular stipules with entire margins. It differs from these taxa by a combination of characters, such as reflexed white trichomes congregated at the petiole apices, ovate floral bracts with basal lobes, subsessile flowers with pale to dark crimson petals and lenticular mericarps with minutely rugulose surfaces when mature.